An empirical study on Green BPM adoption: Contextual factors and performance. Issue 3 (8th July 2020) - Couckuyt, Dries; Van Looy, Amy
Abstract: Business process management (BPM) examines how work is performed in organizations. As environmental sustainability and context awareness are important to organizations, this study addresses two BPM calls. First, it focuses on the ecological impact of business processes. Second, this research recognizes the effect of an organization's business context when applying BPM. We have developed hypotheses to statistically analyze the effect of organization location, sector, size, and competitiveness (i.e., as contextual factors) on Green BPM adoption (RQ1). Additionally, the study reveals which BPM capabilities contribute more to an organization's society‐related performance (RQ2). The research questions were examined by means of a correlation analysis, hypothesis testing, and a regression analysis. The data set contained 100 BPM‐related responses from 403 high‐level managers, working in the United States, the United Kingdom, Australia, and India. For RQ1, we found a strong dependency between Green BPM adoption and organization size and competitiveness. For RQ2, although all BPM capabilities are positively linked to society‐related performance, four of them are of the highest importance, namely: (1) process‐based external relationships; (2) process‐oriented values, attitudes, and behaviors; (3) process‐oriented organization chart; and (4) process‐oriented governance bodies. We conclude with a discussion of these results, and we offer Green BPM decision‐making advice to practitioners.